The effect of cassia sieberiana root bark extract on various experimental gastric ulcer models in rats - Nartey, E.T.; Addo, P.G.; Ofosuhene, M.; Okine, L.K.; Nyarko, A.K. (Journal of Phytomedicine and Therapeutics, 2009)
The antiulcerogenic effects of the root bark extract of C. sieberiana were studied using various gastric ulcer models in rats. This was to support the rational phytotherapeutic use of Cassia sieberiana root bark extract in managing gastric ulcer. The cytoprotective ability of the extract was tested using the HCl/ethanol and the indomethacin-HCl/ethanol induced gastric lesion models. The healing ability of the extract was tested using the acetic acid induced model. Ulcer index, gastric HCl output, mucus production, pepsin activity and volume of gastric secretion were measured. Oral administration of the abstract (500-1000 mg/kg body weight) inhibited the formation of gastric ulcers induced by HCl/ethanol (19-61%). This inhibition was significantly (p <0.05) suppressed by pre-treatment of the experimental rats with indomethacin (30 mg/kg i.p). Oral administration of the extract in acetic acid induced ulcers produced significant dose-dependent healing of the gastric ulcers, significantly decreased total gastric HCl output and also significantly increased gastric barrier mucus production but these were not associated with changes in gastric secretion volume or pepsin activity.